(untitled) (Journal of Medical & Health Sciences Review, 2025)
Mantids (Mantodea: Mantidae) are vital predatory insects in agroecosystems, yet their distribution and morphological variation remain poorly understood in Pakistan. This study aimed to address this knowledge gap by collecting (275) individuals of three mantid species including Tenodera attenuata, Mantis religiosa, and Sphodromantis transcaucasica from seven major Taluka’s of district Mirpurkhas between May and November 2022-2023. Morphological traits, including body and pronotum length, were measured, and sex was determined via genitalia and abdominal segmentation. One-way ANOVA revealed significant differences in total body length between males and females (F = 3234.10, P < 0.001) and among species (F = 3419.33, P < 0.001). Notably, Mantis religiosa had the smallest body size, while Tenodera attenuata had the largest, followed by Sphodromantis transcaucasica. These variations likely reflect ecological adaptations, such as reproductive strategies, prey selection, and habitat preferences. This study provides essential baseline data on mantid distribution, morphology, and ecological significance in Mirpurkhas, highlighting their potential as biological control agents in local agroecosystems and contributing to our understanding of mantid diversity.